Factors Influencing the Interest of Women of Reproductive Age in Using Implant Contraceptives at PMB Rulita Achmad, A.Md.Keb - Iffa, Okta Imtizil; Safitri, Rani (Jurnal EduHealth, 2025)
Implantable contraceptives are highly effective as they can delay or prevent conception for a maximum of three years. Results from implanted contraceptives are as high as 97–99% effective. Finding out what makes pregnant women interested in implanted contraception was the driving force for this research. The research consisted of a cross-sectional analytic survey with 83 participants selected using a non-probability sampling procedure. The data was gathered using a questionnaire and subsequently analyzed using chi-square and spearman tests. An association between husband support (Sig. 0.000 < 0.05) and the interest of reproductive-age women in using implanted contraceptives was found in the data. Additionally, a correlation between interest and health worker information (p-value 0.009 < 0.005) was reported. Females of reproductive age who are interested in using implanted contraceptives do not differ according to age, education, knowledge, parity, or career. Husband support and health worker knowledge are the elements that are connected with the interest of women of childbearing age (PUS) towards the use of implant contraceptives, according to these data. Health care practitioners are encouraged to enhance therapy approaches by include spouses into counseling sessions and helping them choose a strategy of family planning. There is a high expectation that they would dispel myths and misconceptions regarding implanted contraceptives and provide comprehensive community education on the process.